A trajetória de aplicação de tesauros em documentos de arquivo: a criação do microtesauro da Série Inquéritos Policiais do Arquivo Público do Estado do Pará - SANTOS, Adriana Carla Ribeiro dos (Universidade Federal do Pará, 2024)
The research analyzes the development of Knowledge Organization in the Domain of Archival Science, presents as a central discussion, the theoretical and methodological foundations that involve the use of the thesaurus in the context of the web. A more detailed model of organic-functional information is proposed for the Police Inquiries Series of the Public Archive of the State of Pará – APEP, based on the Australian model, with the aid of the Applied Semantic Thesaurus - (THESA). Consider that the Knowledge Organization is an area that contributes significantly to the creation and development of methodologies for information. So, how can we apply Knowledge Organization in the context of systems? In order to answer this question, we started with a methodological approach in three stages: the exploratory phase, fieldwork and data processing and analysis. Results can be used by other institutions. Through the product developed in a precise and representative way of organic- functional information.